Agency work and agency workers - employee representation in Germany and Singapore - Mitlacher, L.; Waring, P.; Burgess, John; Connell, Julia (Group Researching Organisations, Work, Employment and Skills, 2014)
Comparatively new forms of work, such as temporary agency work, have led to changes in employment relations systems resulting in various consequences for temporary agency workers. To date, analysis of such changes and their effects have been quite limited, especially with regard to comparative, international perspectives. Consequently, the intention of this article is to partially address that gap by considering temporary agency work and workers in Germany and Singapore. These countries were selected as both have experienced significant growth in agency work while possessing different features in their employment relations systems. The paper provides insights relevant to the contradictions and tensions inherent in the position of agency workers in the German and Singaporean system of employment relations, making suggestions for a new regulatory approach of the temporary agency industry.